A Comparative Analysis of Challenges in Literary Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines a comprehensive examination of literal and literary translation, detailing the various types of literal translation and providing clear examples for each. It also explains the concept of literary translation, exploring its classifications and analyzing Cholpon’s poem “Beauty”. The study highlights the challenges and parallels encountered during the translation process. Furthermore, it identifies and discusses the three primary challenges in translation: linguistic, cultural, and human challenges. The concept of literary translation is also explored, including its classifications and an analysis of Cholpon’s poem “Beauty” as a case study. This investigation highlights the inherent challenges and potential parallels encountered in achieving a successful and meaningful transfer of ideas across languages. The study further identifies and discusses the three primary challenges in translation: linguistic, cultural, and human challenges, emphasizing the importance of understanding nuances and context. Ultimately, it argues that navigating these complexities is crucial for effective and accurate communication.